Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the sum of the infinite geometric series [tex]\(\sum_{n=1}^{\infty}(-144)\left(\frac{1}{2}\right)^{n-1}\)[/tex], we need to identify the first term and the common ratio of the series.
1. Identify the first term [tex]\(a\)[/tex]:
The given series can be written in a general form for a geometric series:
[tex]\[ \sum_{n=1}^{\infty} a \cdot r^{n-1} \][/tex]
Here, the first term [tex]\(a\)[/tex] is [tex]\(-144\)[/tex].
2. Identify the common ratio [tex]\(r\)[/tex]:
The common ratio [tex]\(r\)[/tex] is the factor by which each term is multiplied to get the next term. In this series, [tex]\(r = \frac{1}{2}\)[/tex].
3. Formula for the sum of an infinite geometric series:
The sum [tex]\(S\)[/tex] of an infinite geometric series [tex]\(\sum_{n=1}^{\infty} ar^{n-1}\)[/tex] is given by the formula:
[tex]\[ S = \frac{a}{1 - r} \][/tex]
This formula applies when the absolute value of the common ratio is less than 1 ([tex]\(|r| < 1\)[/tex]).
4. Substitute the values into the formula:
[tex]\[ a = -144, \quad r = \frac{1}{2} \][/tex]
Plug these into the formula:
[tex]\[ S = \frac{-144}{1 - \frac{1}{2}} \][/tex]
5. Simplify the expression:
[tex]\[ S = \frac{-144}{1 - \frac{1}{2}} = \frac{-144}{\frac{1}{2}} \][/tex]
Dividing by [tex]\(\frac{1}{2}\)[/tex] is equivalent to multiplying by 2:
[tex]\[ S = -144 \times 2 = -288 \][/tex]
Therefore, the sum of the infinite geometric series [tex]\(\sum_{n=1}^{\infty}(-144)\left(\frac{1}{2}\right)^{n-1}\)[/tex] is [tex]\(\boxed{-288}\)[/tex].
1. Identify the first term [tex]\(a\)[/tex]:
The given series can be written in a general form for a geometric series:
[tex]\[ \sum_{n=1}^{\infty} a \cdot r^{n-1} \][/tex]
Here, the first term [tex]\(a\)[/tex] is [tex]\(-144\)[/tex].
2. Identify the common ratio [tex]\(r\)[/tex]:
The common ratio [tex]\(r\)[/tex] is the factor by which each term is multiplied to get the next term. In this series, [tex]\(r = \frac{1}{2}\)[/tex].
3. Formula for the sum of an infinite geometric series:
The sum [tex]\(S\)[/tex] of an infinite geometric series [tex]\(\sum_{n=1}^{\infty} ar^{n-1}\)[/tex] is given by the formula:
[tex]\[ S = \frac{a}{1 - r} \][/tex]
This formula applies when the absolute value of the common ratio is less than 1 ([tex]\(|r| < 1\)[/tex]).
4. Substitute the values into the formula:
[tex]\[ a = -144, \quad r = \frac{1}{2} \][/tex]
Plug these into the formula:
[tex]\[ S = \frac{-144}{1 - \frac{1}{2}} \][/tex]
5. Simplify the expression:
[tex]\[ S = \frac{-144}{1 - \frac{1}{2}} = \frac{-144}{\frac{1}{2}} \][/tex]
Dividing by [tex]\(\frac{1}{2}\)[/tex] is equivalent to multiplying by 2:
[tex]\[ S = -144 \times 2 = -288 \][/tex]
Therefore, the sum of the infinite geometric series [tex]\(\sum_{n=1}^{\infty}(-144)\left(\frac{1}{2}\right)^{n-1}\)[/tex] is [tex]\(\boxed{-288}\)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.